Multiple inflation - Ross, G (1998)
We discuss how, in realistic theories of particle physics, the stages of symmetry breaking may, through gravitational corrections, affect the inflationary potential. As a result there may be several short bursts of inflation leading to observable structure in the spectrum of the generated scalar density perturbations.